Increasing presence via a more immersive VR system increases virtual reality analgesia and draws more attention into virtual reality in a randomized crossover study - Hoffman, Hunter G.; Seibel, Clayton C.; Coron, Lyla; Simons, Laura E.; Drever, Sydney; Le May, Sylvie; Mason, Keira P.; Flor, Herta (Frontiers in Virtual Reality, 2024)
Researchers frequently speculate that Immersive Virtual Reality (VR) diminishes pain by reducing how much attention is available to process nociceptive signals, but attention has rarely been measured in VR analgesia studies. The current study measured how much attention VR uses. Using a repeated measures crossover design, 72 college students (mean = 19 year old) gave pain ratings (0-10 GRS scale) during brief painful but safe and tolerable heat stimulations during No VR, vs. immersive VR vs. semi-immersive VR (treatment order randomized). Compared to semi-immersive VR, during immersive VR, participants reported a significant 25% drop in pain intensity, and a significant 23% increase in fun during the pain stimulus, (p < .001 for each measure). As predicted by an attention mechanism for how VR reduces pain (the distraction hypothesis), participants made significantly more mistakes on an attention-demanding oddnumber divided-attention task during the immersive VR condition than during the less immersive VR condition. Secondary analyses also showed that immersive VR was still effective at higher pain intensity levels, and was widely effective regardless of gender, race, or participant's tendency to catastrophize.